Antiamyloid β toxicity effect of genistein via activation of DAF‐16 and HSP‐16.2 signal pathways in Caenorhabditis elegans. Issue 7 (4th April 2022) - Li, Ke; Zhang, Saiya; Sun, Yiyang; Chen, Yusi; Chen, Wenbo; Ruan, Weibin; Liu, Yanqiang
Abstract: β‐Amyloid toxicity (Aβ) is an important pathological factor of Alzheimer's disease (AD). Studies have shown that genistein can reduce the toxicity of Aβ to a certain extent; however, the specific mechanism is still uncertain. In the study, we applied Caenorhabditis elegans strains expressing Aβ peptides to evaluate the role of genistein inhibiting Aβ toxicity and the undying mechanism. Genistein influencing the sterol metabolism pathway, the HSP‐16.2 pathway, and lipofuscin in different strains of C. elegans were studied using reverse transcription‐polymerase chain reaction, fluorescence labeling, RNA interference (RNAi), and so forth. Our results showed that genistein alleviated the paralysis of transgenic C. elegans strains. Furthermore, in AD C. elegans, genistein reduced the fluorescence of lipofuscin, downregulated the messenger RNA (mRNA) level of vit‐3 and vit‐6 which were related to the sterol metabolism pathway, significantly increased the mRNA level and protein level of HSP‐16.2, increased the nuclear translocation of the DAF‐16 transcription factor and increased the survival rate after heat stress, which was closely associated with HSP‐16.2 levels. However, the paralysis‐alleviating effect of genistein was greatly reduced because of RNAi‐mediated inhibition of hsp‐16.2, indicating that the anti‐Aβ toxicity effect of genistein was greatly dependent on HSP‐16.2. The above results suggest that genistein inhibiting the toxicity of Aβ in C. elegans, is involved in the modulation of the sterol metabolism pathway by promoting transcription factor DAF‐16 translocation into the nucleus, increasing the expression level of HSP‐16.2, and reducing the levels of lipofuscin through its antioxidant activity. Abstract : Relative signal pathways of genistein enhancing resistance to β‐amyloid in Caenorhabditis elegans .